Settlement delays in the money market - Bartolini, Leonardo; Hilton, Spence; McAndrews, James J. (Journal of Banking & Finance, 2010)
We track 38,000 money market trades from execution to delivery and return, and provide a first empirical analysis of settlement delays in financial markets. In accord with the predictions of recent models of strategic settlement of financial claims, we document a tendency by lenders to delay delivery of loaned funds until the afternoon hours. We find banks to follow a simple strategy to manage the risk of account overdrafts, by delaying settlement of large payments relative to that of small payments. More sophisticated strategies such as increasing delays when own liquid balances are low and when dealing with small trading partners play a marginal role. We find evidence of strategic delay also when returning borrowed funds, although we can explain a smaller fraction of the dispersion in delays in the return than in delivery leg of money market lending.